Sekolah Keluarga Berkualitas: Pencegahan Stunting di Kabupaten Sukabumi - Herawati, Tin; Hastuti, Dwi; Yuliati, Lilik Noor; Ryadi, Yusuf; Asikin, Munawar (Jurnal Pengabdian Inovasi Masyarakat Indonesia, 2025)
Human resources are the primary capital in national development and the most important aspect needed to advance a nation. The issue of stunting in Indonesia poses a threat to the development of quality human resources. Families play a crucial role in contributing to societal issues, including stunting. Family empowerment through the Quality Family School aims to provide education to mothers with young children and pregnant women. This program was implemented in two locations: Gede Pangrango Village and Sukamanis Village. A total of 100 participants attended the school. The results of the activity showed an increase in participants' knowledge regarding family resilience, parenting, financial management, child value investment, and family functions.